Porous ceramic laminate and separation membrane

By adding specific elements to the multi-layer structure of the ceramic membrane and controlling its mass ratio, strengthened metal oxides are formed, the problem of peeling the ceramic membrane interface is solved, the peel strength and filtration performance are improved, and efficient permeability is maintained especially when the fluid velocity changes.

JP2025037438APending Publication Date: 2025-03-18SUMITOMO CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023144373
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, multi-layered ceramic membranes are prone to interface peeling problems during application, resulting in an increase in pressure loss when the fluid passes through, affecting filtration performance.

Method used

By adding Al and Fe elements to the first ceramic layer and controlling their mass ratio, a reinforced metal oxide is formed; elements such as Al, Ti, Si and Mg are added to the second ceramic layer to form oxides with high hardness, and the binding force between the two layers is enhanced by controlling the molar ratio of Ti/Al.

Benefits of technology

It significantly improves the peel strength of the ceramic membrane, reduces the pressure loss when the fluid passes through, and maintains efficient filtration performance, especially when the fluid velocity changes from high to low, it can still maintain high permeability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037438000001
    Figure 2025037438000001
  • Figure 2025037438000002
    Figure 2025037438000002
Patent Text Reader

Abstract

To provide a porous ceramic laminate in which two or more layers are laminated, and peeling at the lamination interface is suppressed.SOLUTION: The present invention provides a porous ceramic laminate having a first porous layer and a second porous layer directly laminated on the first porous layer, wherein the first porous layer contains a metal oxide X and also contains the element Al and the element Fe, the mass ratio of Fe / Al in the first porous material is 5.7×10-4 or more and 1.6×10-2 or less, and the second porous layer includes an oxide Y including at least one selected from the group consisting of Al, Ti, Si and Mg.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a porous ceramic laminate and a separation membrane. [Background technology]

[0002] Porous ceramic bodies are used in various fields as membranes having functions such as separation, concentration, or filtration of fluids, such as gases or liquids, such as microfiltration membranes, ultrafiltration membranes, nanofiltration membranes, reverse osmosis membranes, ion exchange membranes, and gas separation membranes.

[0003] For example, Patent Document 1 discloses a monolithic separation membrane structure comprising a substrate made of a porous material and having a plurality of through holes, a first support layer formed on the inner surfaces of the plurality of through holes, and a separation membrane disposed inside the first support layer, the first support layer containing alumina, titania, and at least one of silica and magnesia. Patent Document 1 describes that the strength of the first support layer can be improved by containing the above-mentioned components in the first support layer.

[0004] Furthermore, Patent Document 2 discloses a ceramic porous body obtained by binding ceramic particles with a binder of glass that contains a metal oxide selected from Li2O, Na2O, and the like, with the remainder being SiO2 and unavoidable impurities, and describes that such a ceramic porous body can be used for a long period of time as a filtration filter, etc., even in environments exposed to acids and alkalis. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2015 / 146571 [Patent Document 2] JP 2003-238257 A Summary of the Invention [Problem to be solved by the invention]

[0006] It is important that porous ceramic bodies suitable for use in the above-mentioned fields allow fluids to flow easily through the porous ceramic body while fully performing functions such as separation, i.e., that the pressure loss of the fluid is small, and therefore the porous ceramic body is usually composed of a laminate of two or more layers including a functional layer with a small pore diameter and a support layer with a large pore diameter that supports the functional layer. In a laminate in which two or more layers are laminated, peeling will occur at the interface when a load is applied to the laminate unless the bond at the interface is strong.

[0007] The aforementioned Patent Documents 1 and 2 also disclose a laminate as a structure of a separation membrane, but do not consider peeling at the lamination interface. Therefore, an object of the present invention is to provide a porous ceramic laminate in which two or more types of layers are laminated, in which peeling at the lamination interface is suppressed. [Means for solving the problem]

[0008] The present invention which achieves the above object is as follows. [1] A porous ceramic laminate having a first porous layer and a second porous layer directly laminated on the first porous layer, The first porous layer contains a metal oxide X, and also contains an Al element and an Fe element, and the Fe / Al mass ratio in the first porous layer is 5.7×10 -4 That's it, 1.6 x 10 -2 is as follows: The second porous layer is a porous ceramic laminate containing an oxide Y containing at least one selected from the group consisting of Al, Ti, Si, and Mg. [2] The porous ceramic laminate according to [1], wherein the oxide Y contains an oxide of Al and Ti, and the molar ratio of Ti / Al in the second porous layer is 0.005 or more and less than 0.10. [3] The porous ceramic laminate according to [1] or [2], wherein the first porous layer contains Na element and the mass ratio of Na / Fe in the first porous layer is greater than 0.132 and is 40 or less. [4] The porous ceramic laminate according to any one of [1] to [3], wherein the first porous layer contains elemental Si and has a Si / Fe mass ratio of more than 32.6. [5] The porous ceramic laminate according to any one of [1] to [4], wherein the metal oxide X contains Al2O3. [6] The porous ceramic laminate according to any one of [1] to [5], which is in a tubular or monolithic shape. [7] A separation membrane comprising the porous ceramic laminate according to any one of [1] to [6]. Effect of the Invention

[0009] According to the present invention, it is possible to provide a porous ceramic laminate having improved peel strength between the first porous layer and the second porous layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The porous ceramic laminate of the present invention is a porous ceramic laminate having a first porous layer and a second porous layer directly laminated on the first porous layer, the first porous layer containing a metal oxide X, and also containing Al element and Fe element, and a mass ratio of Fe / Al in the first porous layer is 5.7×10 -4 That's it, 1.6 x 10 -2 The second porous layer contains an oxide Y containing at least one selected from the group consisting of Al, Ti, Si, and Mg.

[0011] (1) First porous layer The first porous layer contains a metal oxide X. The metal oxide X may be one type or two or more types. The metal oxide X preferably contains at least one oxide selected from the group consisting of Al, Ca, Na, Fe, and Si, and more preferably contains Al2O3. The at least one oxide selected from the group consisting of Al, Ca, Na, Fe, and Si includes oxides containing only one type of metal element, as well as composite oxides containing two or more types of metal elements.

[0012] The first porous layer contains Al and Fe elements. The Al and Fe elements may be contained in the form of the metal oxide X described above, or may be contained in a form other than the oxide.

[0013] The Fe / Al mass ratio in the first porous layer is 5.7×10 -4 That's it, 1.6 x 10 -2 The Fe in the first porous layer is likely to form a strong compound (preferably an oxide) with at least one oxide Y selected from the group consisting of Al, Ti, Si, and Mg in the second porous layer, which strengthens the bonding strength between the first porous layer and the second porous layer and increases the peel strength between the two layers. Therefore, the Fe / Al mass ratio is 5.7×10 -4 It is equal to or greater than 1.0×10 -3 More than 2.0×10 is preferable. -3 More preferably, 4.0×10 -3 More preferably, the above is the case. If the amount of Fe in the first porous layer is too large, the compound formed between the first and second porous layers will grow abnormally locally, causing cracks to occur and reducing the strength, which in turn weakens the peel strength between the first and second porous layers. Therefore, the Fe / Al mass ratio should be 1.6×10 -2 is less than or equal to 8.0 x 10 -3 Less than 6.0×10 is preferable. -3 The following is more preferred:

[0014] In addition, the first porous layer preferably contains Na element, and the mass ratio of Na / Fe is preferably more than 0.132 and 40 or less. Na is an element that can act as an auxiliary agent for promoting bonding when the Fe element in the first porous layer and at least one oxide selected from the group consisting of Al, Ti, Si and Mg in the second porous layer form a compound. When the mass ratio of Na / Fe is in the range of more than 0.132, the peel strength between the first porous layer and the second porous layer can be further improved, and the decrease in permeability can be suppressed when the speed of the fluid passing through the laminate of the present invention is switched from a high flow rate to a low flow rate. The mass ratio of Na / Fe is more preferably 0.5 or more, further preferably 1.0 or more, and preferably 2 or more. On the other hand, if the amount of Na in the first porous layer is too large, it may inhibit the bonding of the Fe element, or the compound formed between the first and second porous layers may locally grow abnormally, causing cracks to occur and reducing the strength, thereby reducing the peel strength between the first porous layer and the second porous layer. The mass ratio of Na / Fe is more preferably equal to or less than 30, even more preferably equal to or less than 25, and even more preferably equal to or less than 20. The Na element may be contained as a metal oxide X, or may be contained in a form other than the oxide.

[0015] Furthermore, the first porous layer preferably contains Si element, and the mass ratio of Si / Fe in the first porous layer is preferably more than 32.6. When the mass ratio of Si / Fe is large, the decrease in permeability can be suppressed when the flow rate of the fluid passing through the laminate of the present invention is switched from a high flow rate to a low flow rate. The mass ratio of Si / Fe is more preferably 40 or more, further preferably 50 or more, and even more preferably 60 or more, and the upper limit may be, for example, 90 or less. The Si element may be contained as a metal oxide X, or may be contained in a form other than an oxide.

[0016] The amount of elements contained in the first porous layer can be measured by X-ray fluorescence analysis, and can be measured by quantifying the first porous layer using the FP method using a commercially available X-ray fluorescence analyzer such as ZSX PrimusII (manufactured by Rigaku Corporation).

[0017] The cumulative pore area of ​​the first porous layer in the range of pore diameters of 0.98 to 200 μm is 0.010 to 0.550 m 2 / g, and 0.060 to 0.389 m 2 / g. It is more preferable that the pore diameter D LD-max The log differential pore volume is a value expressed as dV / d(logD) where V is the pore volume, D is the pore diameter, dV is the difference in pore volume between measurement points, and d(logD) is the difference in logarithm of the pore diameter. LD-max can be calculated by measuring the porous ceramic laminate by mercury intrusion porosimetry to obtain the log differential pore volume distribution.

[0018] The first porous layer in the present invention contains the metal oxide X, and also contains Al element and Fe element, and the Fe / Al mass ratio is 5.7×10 -4 That's it, 1.6 x 10 -2 The following commercially available substrates can be used, for example, alumina porous pipe manufactured by Iwao Porcelain Industry Co., Ltd., PM filter tube, AF filter tube, AF-D filter tube manufactured by Nikkato Corporation, etc. It is also possible to adjust the Fe / Al mass ratio in the substrate (first porous layer) by the following method.

[0019] The base material for the first porous layer of the present invention is a mixture containing inorganic particles as a raw material of metal oxide X, a pore-forming agent, and Fe. The raw material obtained by kneading the mixture containing the inorganic particles containing Al2O3 is molded into a predetermined shape, and the molded body obtained is dried and fired to burn off the pore-forming agent. The mass ratio (Fe / Al) of the amount of Fe and Al in the raw material is 5.7×10 -4 That's it, 1.6 x 10 -2 The Fe / Al mass ratio in the substrate was adjusted to 5.7×10 -4 That's it, 1.6 x 10 -2In addition, by setting the average particle size of the inorganic particles to 0.05 to 10 μm and the diameter of the pore-forming agent to 2 to 50 μm, the cumulative pore area of ​​the base material having pore diameters in the range of 0.98 to 200 μm can be set to the above-mentioned 0.010 to 0.550 m2 or less. 2 The average particle size of the inorganic particles is preferably 0.05 to 3 μm, and more preferably 0.1 to 1 μm.

[0020] The inorganic particles used as the raw material of the metal oxide X preferably contain iron oxide, in addition to Al2O3 as described above, so that the raw material contains an Fe component. The inorganic particles preferably further contain one or more selected from the group consisting of calcium hydroxide, sodium hydroxide, and silicon oxide.

[0021] The inorganic particles are aggregates for the base material for the first porous layer. By using inorganic particles having the above-mentioned particle diameter, the aggregate portion becomes a dense ceramic with few pores, and the pore structure can be controlled with a pore-forming agent described later. In a preferred embodiment, the cumulative pore area of ​​pores with diameters of 0.98 to 200 μm is 0.010 to 0.550 m. 2 If the particle size of the inorganic particles is larger than the above range, irregular coarse pores are generated in the gaps between the particles, which may make it difficult to control the pore structure.

[0022] In addition, by appropriately adjusting the Na / Fe mass ratio and Si / Fe mass ratio in the raw material, the Na / Fe mass ratio and Si / Fe mass ratio of the first porous layer in the preferred embodiment can be realized, respectively. That is, for example, when weighing sodium hydroxide and inorganic particles of iron oxide, they may be separated so that the Na / Fe mass ratio is more than 0.132 and not more than 40, and when weighing inorganic particles of silicon oxide and inorganic particles of iron oxide, they may be separated so that the Si / Fe mass ratio is more than 32.6.

[0023] The pore-creating agent is preferably polymer particles controlled to be spherical, which are mixed with the inorganic particles, molded, and then fired to burn off the pore-creating agent, forming pores in the shape of the pore-creating agent, and the cumulative pore area of ​​the pores having a diameter of 0.98 to 200 μm is 0.010 to 0.550 m. 2 A substrate for the first porous layer having a particle size of 1 μm to 50 μm can be obtained. The particle size of the polymer particles used as the pore-creating agent is preferably 2 μm to 50 μm, more preferably 3 μm to 50 μm, and even more preferably 8 μm to 30 μm. By setting the particle size within this range, it becomes possible to create pores with a pore diameter in the range of 0.98 to 200 μm after firing. When a pore-creating agent with a particle size smaller than 2 μm is used, the pore diameter becomes smaller than 0.98 μm, and when the particle size is larger than 50 μm, the strength of the substrate becomes insufficient.

[0024] The polymer constituting the polymer particles can be any polymer such as an acrylic resin or a styrene resin, and commercially available polymer particles can be used.

[0025] The mixing ratio of inorganic particles and pore-creating agent is determined based on the density of the inorganic particle raw material, the density of the pore-creating agent raw material, and the fact that the pore-creating agent burns off after firing. The surface area of ​​the pore-creating agent is set to 0.010 to 0.550 m per 1 g of inorganic particles. 2 It is preferable to adjust the molecular weight so that the molecular weight satisfies the above requirement.

[0026] In addition to the inorganic particles and pore-forming agent described above, the components to be blended into the raw material mixture may include, for example, an organic binder, a dispersant, a surfactant, and water.

[0027] Examples of the organic binder include methyl cellulose, hydroxypropoxyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, and polyvinyl alcohol.

[0028] Examples of dispersants and surfactants include fatty acid salts, alkyl sulfate salts, polyoxyethylene alkyl ether sulfate salts, alkylbenzene sulfonates, alkylnaphthalene sulfonates, alkyl sulfosuccinates, alkyl diphenyl ether disulfonates, alkyl phosphates, polycarboxylates, polyacrylates, aliphatic quaternary ammonium salts, aliphatic amine salts, polyoxyethylene alkyl ethers, polyoxyethylene alcohol ethers, polyoxyethylene glycerin fatty acid esters, polyoxyethylene sorbitan (or sorbitol) fatty acid esters, polyethylene glycol fatty acid esters, alkyl betaines, amine oxides, and cationic cellulose derivatives.

[0029] After kneading the raw material mixture, it is molded into a desired shape to obtain a molded body. A preferred example of the kneading method is a method in which inorganic particles, a pore-forming agent, and water are first mixed to obtain a slurry, and then a binder, a surfactant, and an appropriate amount of water are added to the slurry and kneaded.

[0030] The shape of the molded body (i.e., the shape of the first porous layer) is not particularly limited, and can be various shapes such as a plate shape, a tube shape, a honeycomb shape, or a monolith shape depending on the application. For example, when used as a substrate of a ceramic filter for gas separation, a monolith shape or a honeycomb shape is preferable. The monolith shape means a columnar shape (such as a circular cylinder, a square cylinder, or an elliptical cylinder) having a plurality of holes (preferably a cylindrical shape) penetrating in the axial direction, and the honeycomb shape means a shape in which hollow three-dimensional figures (such as a regular hexagonal cylinder, a square cylinder, or a triangular cylinder) penetrating in the axial direction are stacked without gaps. To mold the raw material into a monolith shape or a honeycomb shape, it is preferable to adopt a molding method such as extrusion molding.

[0031] The obtained molded body is dried by an appropriate drying method and then fired. The drying method is not particularly limited, but a drying method using microwaves, hot air, or the like is preferable. In addition, after drying the molded body, and before firing, a calcination may be appropriately performed to burn and remove the pore-forming agent in the molded body. In general, the calcination temperature may be about 600°C. There is no particular limit to the calcination time, but it is usually about 1 to 10 hours. The calcination atmosphere may be appropriately selected from air, nitrogen, and the like.

[0032] The firing temperature is preferably 1400 to 1600°C, and more preferably 1400 to 1550°C. If the firing temperature is less than 1400°C, sintering may not proceed sufficiently. On the other hand, if the firing temperature exceeds 1600°C, the pores shrink, making it difficult to adjust the pore structure. The firing time is not particularly limited, but is usually about 1 to 10 hours. The firing atmosphere can be appropriately selected from air, nitrogen, and the like.

[0033] The thickness of the first porous layer is preferably 400 to 8000 μm. When the first porous layer has a monolithic or honeycomb shape, the thickness may be an average value of the closest distance between adjacent through holes on a plane perpendicular to the axis.

[0034] (2) Second porous layer The second porous layer contains an oxide Y containing at least one selected from the group consisting of Al, Ti, Si, and Mg. The oxide Y may be one type or two or more types. The oxide Y preferably contains an oxide of Al and Ti. The oxide of Al and Ti may be an oxide of Al (Al2O3) and an oxide of Ti (Ti2O3), or a composite oxide of Al and Ti. Ti is useful for improving the strength of a compound (preferably an oxide) formed by an element in the first porous layer and an element in the second porous layer, and the presence of an oxide of Ti in the second porous layer can strengthen the bond between the first porous layer and the second porous layer, thereby improving the peel strength between them. When the second porous layer contains an oxide of Al and Ti, the molar ratio of Ti / Al in the second porous layer is 0.005 or more and less than 0.10. The molar ratio of Ti / Al is preferably 0.01 or more, more preferably 0.03 or more, and may be 0.09 or less, or may be 0.08 or less.

[0035] The second porous layer may contain one or more oxides containing at least one selected from the group consisting of Fe, Zr, Cr and Y, in addition to oxides containing at least one selected from the group consisting of Al, Ti, Si and Mg. The oxides containing at least one selected from the group consisting of Fe, Zr, Cr and Y include oxides containing only one metal element, as well as composite oxides containing two or more metal elements. Commercially available oxide particles can be used for the oxide containing Ti, and examples of the oxides include STS-21, ST-01, ST-21, ST-31, ST-41, STS-01 and STS-02 manufactured by Ishihara Sangyo Kaisha, Ltd., MT-500B, MT-600B and MT-700B manufactured by Teika Corporation, and TAF-520, TAF-500 and TAF-1500 manufactured by Fuji Titanium Industries Co., Ltd., and STS-21, STS-01 and STS-02 manufactured by Ishihara Sangyo Kaisha, Ltd. are preferred.

[0036] The presence and content ratio of elements contained in the second porous layer can be measured by SEM-EDX analysis, and can be measured by performing a composition analysis of the second porous layer using a commercially available SEM-EDX device such as JSM-7500F (manufactured by JEOL Ltd.).

[0037] Pore ​​diameter D of the second porous layer LD-max is, for example, 0.1 to 2.0 μm, preferably 0.1 to 1 μm, more preferably 0.1 to 0.5 μm, and further preferably 0.2 to 0.4 μm. LD-max As described in the description of the first porous layer, this refers to the pore diameter at which the log differential pore volume value is maximum, and can be obtained by measuring the porous ceramic laminate using mercury intrusion porosimetry.

[0038] The thickness of the second porous layer is, for example, 1 μm to 3 mm, preferably 2 μm to 2 mm, more preferably 3 to 300 μm, even more preferably 20 to 100 μm, particularly preferably 25 to 80 μm, and most preferably 30 to 60 μm. The thickness of the second porous layer can be determined by the following procedure. First, an image of a cross section parallel to the lamination direction of the first porous layer and the second porous layer is obtained. In the image, the total length of the surface of the second porous layer facing the first porous layer is determined to be equal to or smaller than the pore diameter D at which the value of the log differential pore volume of the first porous layer is maximized. LD-max An image is obtained so that the area is 10 times larger than the area of ​​the first porous layer, and only the second porous layer is extracted by image analysis. Then, the thickness (length in the stacking direction) of the second porous layer in the obtained image is measured at five or more points, and the average thickness of the measured points is calculated. Note that the cross section parallel to the stacking direction of the first porous layer and the second porous layer can be, for example, a cross section perpendicular to the longitudinal direction of the stack (for example, the axial direction when the stack is tubular or monolithic).

[0039] (3) Porous ceramic laminate (3-1) Structure and shape The porous ceramic laminate of the present invention includes a first porous layer and a second porous layer, and the second porous layer is directly laminated on the first porous layer. Directly laminated means that the first porous layer and the second porous layer are laminated without any other layer. As long as a part of the second porous layer is in contact with the first porous layer, the remaining part may be laminated on the first porous layer via air existing due to pores present on the surface of the first porous layer or inorganic particles other than the metal oxide particles constituting the second porous layer. The part where the second porous layer and the first porous layer are in contact may be the pore part of the pores present on the surface of the first porous layer. In addition, in the porous ceramic laminate of the present invention, the pore diameter D of the first porous layer may be 100 μm or more. LD-max is the pore diameter D of the second porous layer LD-max Larger is preferred.

[0040] The shape of the porous ceramic laminate is not particularly limited, and examples thereof include plate-like, tubular, honeycomb-like, and monolithic shapes. A tubular, honeycomb-like, or monolithic shape is preferable, and a monolithic shape is preferable, particularly when used as a substrate for a ceramic filter for gas separation. The monolithic shape means a columnar (cylindrical, rectangular, elliptical, etc.) shape having a plurality of holes (preferably cylindrical) penetrating in the axial direction, and the honeycomb shape means a shape in which hollow three-dimensional figures (regular hexagonal, rectangular, triangular, etc.) penetrating in the axial direction are stacked without gaps. When the porous ceramic laminate is tubular, the second porous layer is preferably formed only on the inner circumferential surface, only on the outer circumferential surface, or both the inner circumferential surface and the outer circumferential surface of the tube, more preferably formed only on the inner circumferential surface or only on the outer circumferential surface, and even more preferably formed only on the inner circumferential surface. When the porous ceramic laminate is monolithic, the second porous layer is preferably formed only on the inner surface of each through hole of the monolithic shape.

[0041] The thickness (average value) of the porous ceramic laminate is, for example, 450 to 10,000 μm, and more preferably 500 to 6,000 μm. When the porous ceramic laminate has a monolithic or honeycomb shape, the thickness may be the average value of the closest distance between adjacent through holes on a plane perpendicular to the axis. The length of the porous ceramic laminate in the longitudinal direction is, for example, 50 to 5000 mm. The length in the longitudinal direction means, for example, the length of the long side in the case of a plate shape, and the length in the axial direction in the case of a tube shape, honeycomb shape, or monolith shape. When the porous ceramic laminate is tubular, the outer diameter is, for example, 5 mm to 20 mm, and the inner diameter of the tube is, for example, 1 mm to 15 mm. When the porous ceramic laminate is honeycomb or monolithic, that is, when it has a plurality of through holes, the outer diameter is, for example, 5 mm to 100 mm, and the inner diameter of each through hole (particularly a cylindrical shape) is, for example, 0.1 mm to 10 mm.

[0042] (3-2) Properties of porous ceramic laminates (3-2-1) Peel strength The peel strength between the first and second porous layers in the porous ceramic laminate of the present invention can be evaluated by measuring the pencil hardness from the second porous layer side of the porous ceramic laminate under the conditions described in the Examples. The second porous layer is a layer containing a metal oxide and usually has a high hardness, so the interface between the first and second porous layers breaks first in the pencil hardness test. Therefore, the peel strength between the first and second porous layers can be evaluated with the hardness calculated by this measurement. The pencil hardness evaluated as described in the Examples is preferably harder than F, more preferably 2H or more, and even more preferably 4H or more, and the upper limit may be 9H.

[0043] (3-2-2) Permeance The porous ceramic laminate of the present invention can also reduce the pressure loss of a fluid, and can achieve a flow rate of 1.0 m as evaluated in the Examples described later. 3 / h permeance is 1.00×10 -5 m 3 / (m 2sec Pa), and preferably 3.00×10 -5 m 3 / (m 2 ·sec·Pa), and more preferably 1.00×10 -4 m 3 / (m 2 ·sec·Pa) or more, and the upper limit is not particularly limited, but for example, 1.0×10 -3 m 3 / (m 2 sec Pa).

[0044] (3-2-3) Permeance maintenance rate when fluid flow velocity decreases In addition, according to the examples described later, the flow rate of the fluid flowing through the porous ceramic body is 1.0 m 3 Permeance at 0.5m / h 3 The permeance maintenance rate, obtained by dividing the rate by the permeance at 100 / h, can be 1.2 or less, preferably 1.18 or less, more preferably 1.10 or less, and even more preferably 1.04 or less, and the lower limit may be 1.0.

[0045] (3-3) Manufacturing method of porous ceramic laminate The porous ceramic laminate of the present invention contains the metal oxide X, and also contains Al element and Fe element, and the Fe / Al mass ratio is 5.7×10 -4 That's it, 1.6 x 10 -2 The first porous layer substrate is prepared so that the cumulative pore area of ​​the first porous layer substrate having a pore diameter of 0.98 to 200 μm is 0.010 to 0.550 m2, and the cumulative pore area of ​​the first porous layer substrate having a pore diameter of 0.98 to 200 μm is 0.010 to 0.550 m2. 2 / g. In particular, the D LD-max is the D of the second porous layer LD-max When the ratio is 10 times or more, it is preferable to subject the substrate for the first porous layer to a water- and oil-repellent treatment, and to apply a slurry containing the oxide Y to the surface of the substrate for the first porous layer that has been treated to be water- and oil-repellent.

[0046] In a preferred embodiment, a porous substrate satisfying the above conditions is used, the substrate is treated to be water- and oil-repellent, and a slurry containing metal oxide Y is applied to the water- and oil-repellent treated surface, thereby preventing the slurry from entering the pores of the substrate when the pore diameters of the first porous layer and the second porous layer are significantly different.

[0047] Methods of water and oil repellency include spray coating, dip coating, bar coating, suction coating, ultrasonic spraying, brush coating, squeegee coating, spray coating, etc. The composition of the water and oil repellent is not limited, but for example, paraffin-based water and oil repellent, fluorine-based water and oil repellent, polysiloxane-based water and oil repellent can be used. Fluorine-based water and oil repellent includes those having a perfluoroalkyl group and those having a perfluoropolyether structure.

[0048] In a preferred embodiment, the Ti / Al ratio in the second porous layer of the porous ceramic laminate of the present invention can be controlled by controlling the Ti / Al ratio in the slurry containing the metal oxide Y to be 0.005 or more and less than 0.10.

[0049] The metal oxide Y contained in the slurry may be one type or two or more types, and it is sufficient that at least one type selected from the group consisting of Al, Ti, Si, and Mg is contained in the metal oxide Y. The metal oxide Y contained in the slurry preferably contains any one of TiO2, Al2O3, and a composite oxide containing Ti and Al.

[0050] The average particle size of the metal oxide Y contained in the slurry is preferably, for example, 0.01 to 2 μm. In particular, the average particle size of a metal oxide containing Al (e.g., Al2O3, or a composite oxide containing Ti and Al, etc.) is preferably 0.1 to 2 μm, and the average particle size of a metal oxide containing Ti (e.g., TiO2, etc.) is preferably 0.01 to 0.1 μm. The particle size distribution of the metal oxide can be measured using a small-angle X-ray scattering method when the average particle size is about 0.1 μm or less, and can be measured using a laser diffraction / scattering type particle size distribution measuring device when the average particle size is about 0.1 μm or more. The average particle size may be a diameter equivalent to 50% cumulative on a volume basis.

[0051] The concentration of the metal oxide Y in the slurry is, for example, 2 mass % or more and 22 mass % or less, and preferably 4 mass % or more and 17 mass % or less.

[0052] The slurry preferably contains, in addition to the metal oxide Y, a solvent, a thickener, and a dispersant. The solvent may be water or an organic solvent. Examples of the thickener include methyl cellulose, hydroxyethyl methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyalkylene oxide, polyvinyl alcohol, sodium polyacrylate, polyvinylpyrrolidone, polyacrylamide, polydimethylaminoethyl methacrylate, etc. The concentration of the thickener in the slurry is, for example, 0.5% by mass or more and 5% by mass or less, and preferably 1% by mass or more and 4% by mass or less. The dispersant can suppress the aggregation of metal oxide particles in the slurry. The dispersant may be any of cationic surfactants, anionic surfactants, nonionic surfactants, and amphoteric surfactants. Among them, anionic surfactants such as polycarboxylate ammonium salts and polycarboxylate amine salts are preferred, and SN Dispersant 5020, SN Dispersant 5023, SN Dispersant 5027, SN Dispersant 5468, Noparfa D-6010, Nopcol 5200, Nopcosant RFA, Nopcosperse 6100, and Nopcosperse 6150 manufactured by San Nopco Co., Ltd. may be used. The concentration of the dispersant in the slurry is, for example, 0.1% by mass or more and 3% by mass or less, and preferably 0.3% by mass or more and 1% by mass or less.

[0053] After the slurry is applied, a heat treatment may be performed. The heat treatment temperature is, for example, 1000° C. or more and 1500° C. or less, and the heat treatment time is, for example, 1 hour or more and 8 hours or less.

[0054] (4) Separation membrane The porous ceramic laminate of the present invention can be used as a microfiltration membrane, an ultrafiltration membrane, or a nanofiltration membrane, and can be further laminated with a functional membrane as necessary to be used as a microfiltration membrane, an ultrafiltration membrane, a nanofiltration membrane, a reverse osmosis membrane, an ion exchange membrane, a separation membrane for gases, etc.

[0055] Examples of the functional membrane described above include zeolite, MOF (Metal Organic Frameworks), porous silica membrane, and porous alumina membrane. A separation membrane with a functional layer can be produced by applying a liquid containing inorganic particles or MOF that constitute a functional layer to the surface of the ceramic porous laminate obtained by the present invention and reacting it. The synthesis conditions can be appropriately selected depending on the functional layer to be laminated, and may be, for example, 80 to 800°C for 1 to 72 hours. EXAMPLES

[0056] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples, and can of course be modified within the scope of the above and below-mentioned aims, and all such modifications are within the technical scope of the present invention.

[0057] The materials used in the following Examples and Comparative Examples and the resulting porous ceramic laminates were evaluated by the following methods.

[0058] (1) Measurement of metal content in the substrate (first porous layer) The Fe, Al, Na, and Si contents of the substrate (first porous layer) were measured using an X-ray fluorescence analyzer (XRF, manufactured by Rigaku Corporation, ZSX PrimusII) by the FP method.

[0059] (2) Method for measuring particle size of metal oxides The particle size distribution of the alumina used in the examples and comparative examples was measured using a laser diffraction / scattering particle size distribution measuring device (Microtrac MT3300EX II, 0.2 mass% aqueous solution of sodium hexametaphosphate, manufactured by Microtrac Corporation), and the volume-based cumulative 50% equivalent diameter was measured.

[0060] (3) Cumulative pore area of ​​substrate with pore diameter of 0.98 to 200 μm The substrate was dried at 120° C. for 4 hours, and then the cumulative pore area was measured by mercury intrusion porosimetry using an Autopore IV9520 (manufactured by Micromeritics). The details of the measurement conditions are as follows. Hg Surface Tension:480.000dynes / cm Hg Density: 13.5335g / mL Adv. Contact Angle:140.000degrees Rec. Contact Angle:140.000degrees Pen. Constant: 11.007μL / pF Pen. Weight: 1.0000g Stem Volume: 0.3920mL Max. Head Pressure: 4.4500psia Pen. Volume: 1.0000mL Assembly Weight: 141.0000g Low Pressure(Evacuation Pressure):50μmHg Evacuation Time: 10 seconds Mercury Filling Pressure:1.03psia Equilibration Time: 10 seconds High Pressure(Evacuation Time):10secs Maximum Intrusion Volume:0mL / g

[0061] (4) Pencil hardness measurement The porous ceramic laminates obtained in the examples and comparative examples were evaluated according to JIS K5600 General Test Method for Paint Scratch Hardness (Pencil Method) 5-4. A pencil hardness tester (Yasuda Seiki Seisakusho Co., Ltd. 533-M1, weight: 750g, pencil moving speed: 1mm / sec) was used to draw a line with a soft pencil (Mitsubishi Pencil Co., Ltd.: Mitsubishi Uniseries 6B-9H) on the surface of the laminate (the surface opposite to the first porous ceramic layer), and the surface was observed using a digital microscope (Keyence Corporation: VHX-5000), and the hardness just before the hardness at which peeling, dents, or scratches were observed was evaluated as the hardness of the sample.

[0062] (5) Permeance measurement Air was blown from the outside of the porous ceramic laminate sample at a depth of 1.0 m. 3 The air was allowed to flow at a constant flow rate of 100 / h, and the air that permeated from the inside of the sample was allowed to flow downstream. At this time, the pressure difference between the upstream and downstream sides was measured. The measurement results were converted using the following formula to obtain the permeance. Note that a higher permeance value means a lower pressure loss.

[0063]

number

[0064] (6) Evaluation of permeance maintenance rate when gas flow velocity decreases Air was blown from the outside of the porous ceramic laminate sample at a distance of 0.5 m. 3 / h, and 1.0m 3 The air was passed through the sample at a constant flow rate of 1.0 m / h, and the air that had permeated through the sample was passed downstream. At this time, the pressure difference between the upstream and downstream sides was measured. From the measurement results, the permeance of each side was calculated using an equation similar to that of equation (1) above. 3 / h permeance at low flow rate of 0.5m 3 The permeance maintenance rate when the gas flow rate is reduced was calculated by dividing the permeance at the time of gas flow rate reduction by the permeance at the time of gas flow rate reduction at 100 / h. The lower the permeance maintenance rate, the more it is possible to suppress the reduction in permeance when the gas flow rate is reduced.

[0065] Example 1 The base material (first porous layer) is a porous material having a pore diameter of 0.98 to 200 μm and a cumulative pore area of ​​0.102 m 2A commercially available ceramic substrate E1 (cylinder with an inner diameter of 6.9 mm, an outer diameter of 10.0 mm, and a length of 10 cm, with Fe / Al mass ratio, Na / Fe mass ratio, and Si / Fe mass ratio as shown in Table 1) containing Al2O3 was prepared. The substrate was dipped in a water repellent SH Conc (containing fluororesin and petroleum-based hydrocarbons) manufactured by Columbus Co., Ltd., and dried at room temperature for 12 hours or more. Next, alumina powder AKP-3000 manufactured by Sumitomo Chemical Co., Ltd. and titanium oxide slurry (STS-21: manufactured by Ishihara Sangyo Kaisha, Ltd., 40 wt%) were mixed so that the molar ratio of Ti / Al was 0.0336. The volume-based cumulative 50% equivalent diameter of the alumina powder AKP-3000 was about 0.67 μm, and the X-ray particle diameter (catalog value) of the titanium oxide was 20 nm. The mixture of the alumina powder and the titanium oxide slurry was mixed with hydroxypropyl methylcellulose 65SH-30000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, SN Dispersant 5468 as a dispersant, and water to prepare a slurry. The concentrations of alumina, thickener, and dispersant in the slurry were 5 wt%, 1.5 wt%, and 0.5 wt%, respectively. The upper and lower ends of the substrate (after the water repellent treatment) were sealed so that the slurry would not enter the inner peripheral surface of the substrate, and the substrate was dip-coated with the slurry. Thereafter, the substrate with the slurry applied to the outer peripheral surface was heat-treated at 1200°C for 3 hours to obtain a porous ceramic laminate in which a second porous layer (hardened layer of the slurry) was formed on the substrate (first porous layer).

[0066] Example 2 The base material (first porous layer) is a porous material having a cumulative pore area of ​​0.389 m2 with pore diameters of 0.98 to 200 μm. 2 A porous ceramic laminate of Example 2 was obtained in the same manner as in Example 1, except that a commercially available ceramic substrate E2 containing Al2O3 (cylindrical with an inner diameter of 7.0 mm, an outer diameter of 10.0 mm, and a length of 10 cm, with an Fe / Al mass ratio, a Na / Fe mass ratio, and a Si / Fe mass ratio as shown in Table 1) was used, with the weight of Al2O3 being 7.0 mm / g.

[0067] Example 3 The base material (first porous layer) is a porous material having a pore diameter of 0.98 to 200 μm and a cumulative pore area of ​​0.060 m2 A porous ceramic laminate of Example 3 was obtained in the same manner as in Example 1, except that a commercially available ceramic substrate E3 containing Al2O3 (having an inner diameter of 7.2 mm, an outer diameter of 9.5 mm, and a length of 10 cm, and having an Fe / Al mass ratio, a Na / Fe mass ratio, and a Si / Fe mass ratio as shown in Table 1) was used, in which the weight percent of the porous ceramic substrate E3 was 7.2 g / g.

[0068] Example 4 A porous ceramic laminate of Example 4 was obtained in the same manner as in Example 2, except that the Al in the alumina powder and the Ti in the titanium oxide slurry were mixed so that the molar ratio of Ti / Al was 0.0130.

[0069] Example 5 A porous ceramic laminate of Example 5 was obtained in the same manner as in Example 2, except that the Al in the alumina powder and the Ti in the titanium oxide slurry were mixed so that the molar ratio of Ti / Al was 0.0555.

[0070] Example 6 A porous ceramic laminate of Example 6 was obtained in the same manner as in Example 3, except that the Al in the alumina powder and the Ti in the titanium oxide slurry were mixed so that the molar ratio of Ti / Al was 0.00645.

[0071] Example 7 A porous ceramic laminate of Example 7 was obtained in the same manner as in Example 3, except that the Al in the alumina powder and the Ti in the titanium oxide slurry were mixed so that the molar ratio of Ti / Al was 0.0197.

[0072] Example 8 A porous ceramic laminate of Example 8 was obtained in the same manner as in Example 3, except that the Al in the alumina powder and the Ti in the titanium oxide slurry were mixed so that the molar ratio of Ti / Al was 0.0709.

[0073] Comparative Example 1 The porous ceramic laminate of Comparative Example 1 was obtained in the same manner as in Example 1, except that a commercially available ceramic substrate containing Al2O3 (cylindrical in shape with an inner diameter of 6.0 mm, an outer diameter of 9.9 mm, and a length of 10 cm, with a cumulative pore volume of 0.12 mL / g with pore diameters of 0.98 to 200 μm and a mass ratio of Fe / Al, Na / Fe, and Si / Fe as shown in Table 1) was used as the substrate (first porous layer).

[0074] Comparative Example 2 The base material (first porous layer) is a porous material having a pore diameter of 0.98 to 200 μm and a cumulative pore area of ​​0.0010 m 2 A porous ceramic laminate of Comparative Example 2 was obtained in the same manner as in Example 1, except that a commercially available ceramic substrate containing Al2O3 (a monolithic substrate (19 channels) with an inner diameter of 3.3 mm, an outer diameter of 25.4 mm, and a length of 10 cm, with the Fe / Al mass ratio, Na / Fe mass ratio, and Si / Fe mass ratio as shown in Table 1) was used, with the weight of the porous ceramic laminate being 1.5 g / g.

[0075] The results are shown in Table 1.

[0076] [Table 1]

[0077] Furthermore, the following measurements were carried out for the examples and comparative examples. (7) Measurement of pore distribution of the first and second porous layers The entire porous ceramic laminate was measured in the same manner as in the measurement by mercury intrusion method described in (3) above. In the log differential pore volume distribution with the horizontal axis representing the pore diameter, one peak was observed in the measurement of the substrate alone, whereas two peaks were observed in the measurement of the entire porous ceramic laminate. The peak (maximum value of the log differential pore volume) observed in the measurement of the substrate alone gave the pore diameter D LD-max The D of the second porous layer was evaluated, and the peak on the lower pore diameter side of the two peaks observed in the observation of the entire porous ceramic laminate was determined to be the D of the second porous layer. LD-max was evaluated.

[0078] (8) Thickness of the second porous layer The cylindrical porous ceramic laminate was embedded in resin and polished to obtain a cross section perpendicular to the axial direction (i.e., a cross section parallel to the stacking direction of the first porous layer and the second porous layer), which was then observed with a scanning electron microscope (SEM). An image was obtained so that the total length of the surface of the second porous layer on the first porous layer side was 1.5 mm or more in the circumferential direction, and only the second porous layer was extracted by image analysis. The thickness (length in the stacking direction) of the second porous layer in the obtained image was then measured at five or more points, and the average value of the thicknesses measured at the multiple points was taken as the thickness of the second porous layer.

[0079] As a result of the measurement according to (7) above, the pore diameter D of the first porous layer LD-max In Examples 2, 4, and 5, the pore diameter was 1.5 μm, in Examples 3, 6, 7, and 8, the pore diameter was 15 μm, in Example 1, the pore diameter was 8.5 μm, and in Comparative Example 1, the pore diameter D LD-max The results were as follows: Example 2: 0.41 μm, Example 3: 0.27 μm, Example 1: 0.27 μm, Example 4: 0.46 μm, Example 5: 0.37 μm, Example 6: 0.28 μm, Example 7: 0.27 μm, Example 8: 0.30 μm, and Comparative Example 1: 0.28 μm.

[0080] As a result of measuring the thickness of the second porous layer according to (8) above, the thickness was 34.8 μm in Example 3, 35.9 μm in Example 1, and 53.1 μm in Comparative Example 1.

Claims

1. A porous ceramic laminate having a first porous layer and a second porous layer directly laminated on the first porous layer, The first porous layer contains a metal oxide X, and also contains an Al element and an Fe element, and the Fe / Al mass ratio in the first porous layer is 5.7×10 -4 That's it, 1.6 x 10 -2 is as follows: The second porous layer is a porous ceramic laminate containing an oxide Y containing at least one selected from the group consisting of Al, Ti, Si, and Mg.

2. 2. The porous ceramic laminate according to claim 1, wherein the oxide Y contains an oxide of Al and Ti, and the molar ratio of Ti / Al in the second porous layer is 0.005 or more and less than 0.

10.

3. 3. The porous ceramic laminate according to claim 1, wherein the first porous layer contains Na element, and a mass ratio of Na / Fe in the first porous layer is greater than 0.132 and is 40 or less.

4. 3. The porous ceramic laminate according to claim 1, wherein the first porous layer contains elemental Si, and a mass ratio of Si / Fe in the first porous layer is greater than 32.

6.

5. The metal oxide X is Al 2 O 3 The porous ceramic laminate according to claim 1 or 2, comprising:

6. 3. The porous ceramic laminate according to claim 1, which is in the form of a tube or a monolith.

7. A separation membrane comprising the porous ceramic laminate according to claim 1 or 2.

Citation Information

Patent Citations

  • Porous ceramic body and method of manufacturing glass used for binder thereof

    JP2003238257A

  • Monolithic separation membrane structure and method for producing same

    WO2015146571A1